2023
DOI: 10.31219/osf.io/5ankf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Worldwide Survey on The Practices and Perceptions of Submaximal Fitness Tests in Team Sports

Abstract: Purpose: To survey team-sports practitioners on current practices and perceptions of submaximal fitness tests (SMFT). Methods: A convenience sample of team-sports practitioners completed an online survey (September to November 2021). Descriptive statistics was used to obtain information of frequencies. A mixed-model quantile (median) regression was employed to assess the differences between perceived influence of extraneous factors. Results: A total of 66 practitioners (74 protocols) from 24 countries complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…The reliability of HRex, as observed in this study (TE ranging from 1.0 to 1.6 % points, and ICC values ranging from 0.92 to 0.96), lies within the prediction interval ranges of a recent meta-analysis exploring its measurement properties in team sports 27 . Building on these insights 27 , we demonstrated that exercise intensity during the SMFT has no meaningful effects on HRex reliability (Table 2), suggesting that practitioners can choose from a range of fixed intensities that best suits their training targets (e.g., integrated into the warm-up 19 , individualised approach 5 ) and are feasible to be routinely administered in a standardised fashion. Further, although collection timeframes do not appear to affect reliability 27 , using the last 30-60 s of exercise is advisable because it is often less influenced by outliers 27 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The reliability of HRex, as observed in this study (TE ranging from 1.0 to 1.6 % points, and ICC values ranging from 0.92 to 0.96), lies within the prediction interval ranges of a recent meta-analysis exploring its measurement properties in team sports 27 . Building on these insights 27 , we demonstrated that exercise intensity during the SMFT has no meaningful effects on HRex reliability (Table 2), suggesting that practitioners can choose from a range of fixed intensities that best suits their training targets (e.g., integrated into the warm-up 19 , individualised approach 5 ) and are feasible to be routinely administered in a standardised fashion. Further, although collection timeframes do not appear to affect reliability 27 , using the last 30-60 s of exercise is advisable because it is often less influenced by outliers 27 .…”
Section: Discussionsupporting
confidence: 82%
“…Building on these insights 27 , we demonstrated that exercise intensity during the SMFT has no meaningful effects on HRex reliability (Table 2), suggesting that practitioners can choose from a range of fixed intensities that best suits their training targets (e.g., integrated into the warm-up 19 , individualised approach 5 ) and are feasible to be routinely administered in a standardised fashion. Further, although collection timeframes do not appear to affect reliability 27 , using the last 30-60 s of exercise is advisable because it is often less influenced by outliers 27 . For example, quantifying HRex with a lower number of data points (i.e., peak, fixed value) may result in erroneous results due to measurement noise or HR spikes.…”
Section: Discussionmentioning
confidence: 94%